Effects of Ramadan intermittent fasting on gut microbiome: is the diet key? - Saglam, Duygu; Colak, Gozde Aritici; Sahin, Eray; Ekren, Berkay Yekta; Sezerman, Ugur; Bas, Murat (Frontiers in Microbiology, 2023)
Much research has been conducted regarding the impact of diet on the gut microbiota. However, the effects of dietary habits such as intermittent fasting are unclear. The aim of this study was to investigate the effect of intermittent fasting during Ramadan on the gut microbiota. The study was conducted on 12 healthy adult individuals who practiced fasting 17 hours per day for 29 consecutive days during Ramadan month. To determine the individuals' dietary intakes, a three-day dietary record was kept at the beginning and end of the study. Reads that passed quality filtering were clustered, and custom-prepared 16S rRNA gene regions of bacteria associated with the human microbiome were used as a reference. Consensus sequences were created and genus level taxonomic annotations were determined using a sequence identity threshold of 95%. The correlations between the dietary intake measurements of the participants and the respective relative abundance of bacterial genera were investigated. The results showed that Firmicutes were higher in abundance in the gut microbiota before fasting among participants, while they were significantly lower in abundance at the end of Ramadan fasting (p < 0.05). Proteobacteria were significantly higher in abundance at the end of the Ramadan month (p < 0.05). Fasting was associated with a significant decrease in levels of seven genera: